Incidence and Predictors of Valgus Tibiotalar Tilt after Progressive Collapsing Foot Deformity Reconstruction using Subtalar Fusion. Issue 4 (November 2022) - Kim, Jaeyoung; Rajan, Lavan; Mizher, Rami; Srikumar, Syian; Fuller, Robert; Henry, Jensen K.; Kumar, Prashanth; Potter, Hollis; Johnson, A. Holly; Demetracopoulos, Constantine A.; Ellis, Scott J.; Deland, Jonathan T.; et al.
Category: Ankle; Ankle Arthritis; Hindfoot; Midfoot/Forefoot; Other Introduction/Purpose: Subtalar fusion is a powerful option for correcting hindfoot deformity in progressive collapsing foot deformity (PCFD). Despite successful correction through subtalar fusion, the development of valgus tibiotalar tilt at the ankle joint has been documented as a significant complication. This can be detrimental since abnormal forces on the ankle joint can induce cartilage wear and subsequent ankle arthritis over time. However, the incidence of valgus tilt of the ankle following subtalar fusion for PCFD reconstruction has not been extensively studied, and little is known about its etiological factors. The purpose of this study was to define the incidence of valgus tibiotalar tilt after subtalar fusion for PCFD reconstruction, and to determine if any demographic and radiographic parameters predict which patients develop this complication. Methods: This study reviewed 59 patients (median age: 59 years) who underwent PCFD reconstruction with subtalar fusion and had pre-and postoperative weightbearing anteroposterior radiographs of the ankle in the registry. Patients with a tibiotalar tilt prior to surgery were excluded. On standard weightbearing radiographs, the talonavicular coverage angle, talo-1st metatarsal angle, calcaneal pitch, and hindfoot moment arm (HMA), and medial distal tibial angle were measured. Weightbearing computed tomography (WBCT) was used to determine the presence of preoperative sinus tarsi or calcaneofibular bony impingement. A radiologist evaluated the superficial and deep deltoid ligaments using magnetic resonance imaging (MRI). Postoperative valgus tibiotalar tilt was defined as tilt >2 degrees. Univariate regression analysis was used to identify the factors associated with development of postoperative valgus tibiotalar tilt. These factors included age, gender, BMI, as well as concomitant procedures, radiographic parameters, lateral bony impingement on WBCT, and deltoid ligament status on MRI. Results: A total of 17 patients (28.8%) developed postoperative valgus tibiotalar tilt at a mean of 7.7 (range, 2-31) months. Eight (47.1%) of the 17 patients developed valgus tibiotalar tilt (mean talar tilt of 5.3 degrees, range: 4-8) on postoperative weightbearing within 3 months. In bivariate analysis, male gender and preoperative HMA were significantly associated with development of valgus tibiotalar tilt (Table 1). Univariate logistic regression demonstrated that preoperative HMA was associated with postoperative valgus tibiotalar tilt (odds ratio 1.06, P = .026), with a 6% increase in risk per millimeter of increased HMA. Deltoid ligament status on MRI and concomitant procedures on other joints including fusion did not correlate with postoperative valgus tibiotalar tilt. Conclusion: The incidence of valgus tibiotalar tilt after subtalar fusion in PCFD reconstruction was 28.8% in this study. Preoperative valgus hindfoot alignment rather than the condition of the deltoid ligament was a significant predictor of postoperative valgus tibiotalar tilt. Our findings indicate that surgeons should be cognizant of patients with a greater degree of hindfoot valgus and of their propensity to develop a valgus ankle deformity. Additionally, our relatively high incidence of valgus tibiotalar tilt suggests that weightbearing ankle radiographs should be included in the initial and subsequent follow-up of PCFD patients with hindfoot valgus treated with subtalar fusions.